2017
DOI: 10.1007/s11548-017-1630-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of three-dimensional models of the distal femur created from surgical navigation point cloud data for intraoperative and postoperative analysis of total knee arthroplasty

Abstract: The results demonstrated good correspondence with the distal femoral morphology even in cases of sparse datasets. Application of this technique will allow for measurement of mismatch between pre- and postoperative femurs retrospectively on any case done using the surgical navigation system and could be integrated into the surgical navigation unit to provide real-time feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…69 Magnetic resonance imaging-based 3D SSM may be able to predict the need for knee joint arthroplasty (total knee arthroplasty) 70 and has been used to correlate femur shapes derived from preoperative MRI and intraoperative measurements for total knee arthroplasty patients. 71 Magnetic resonance imaging-derived 3D SSM has shown an association between the patella and femur bone shape features and the patellofemoral joint degeneration at 3 years. 72 Applied to the hip, MRI-based 3D SSM has been used to measure longitudinal variations in proximal femur shape and their associations with hip OA.…”
Section: Bone Shape Modeling and Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 Magnetic resonance imaging-based 3D SSM may be able to predict the need for knee joint arthroplasty (total knee arthroplasty) 70 and has been used to correlate femur shapes derived from preoperative MRI and intraoperative measurements for total knee arthroplasty patients. 71 Magnetic resonance imaging-derived 3D SSM has shown an association between the patella and femur bone shape features and the patellofemoral joint degeneration at 3 years. 72 Applied to the hip, MRI-based 3D SSM has been used to measure longitudinal variations in proximal femur shape and their associations with hip OA.…”
Section: Bone Shape Modeling and Kinematicsmentioning
confidence: 99%
“…A recent study revealed rapid bone shape changes at 3 months after acute ACL injury using MRI-based 3D SSM 69 . Magnetic resonance imaging–based 3D SSM may be able to predict the need for knee joint arthroplasty (total knee arthroplasty) 70 and has been used to correlate femur shapes derived from preoperative MRI and intraoperative measurements for total knee arthroplasty patients 71 . Magnetic resonance imaging–derived 3D SSM has shown an association between the patella and femur bone shape features and the patellofemoral joint degeneration at 3 years 72 .…”
Section: Bone Shape Modeling and Kinematicsmentioning
confidence: 99%
“…4 After segmentation of the CT scan images, an SSM of the selected patient population was generated using an approach described by Lamecker and Zachow. 11,12 Thereby, common anatomical landmarks, such as the inferior, middle, and superior meatus, the nasal septum, the isthmus nasi, and the nasopharynx were manually identified in all patient-specific geometries. All patientspecific geometries were mirrored, so that 50 individual cavities per side of the nose were included in the SSM.…”
Section: Introductionmentioning
confidence: 99%